Comparison of Students' Covariational Reasoning Based on Differences in Field-Dependent and Field-Independent Cognitive Style - Ulumul Umah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
Students’ difficulty in calculus can be related to their ability in covariational reasoning in school or college. Reasoning process involves high-level cognition. Nevertheless, the relationship between cognitive style and covariational reasoning has not been investigated more specifically. Cognitive style in this study was characterized by field-dependent and field-independent category. This paper describes the covariational reasoning process of field-dependent and field-independent students while constructing the graph of dynamic events. Students’ cognitive style data obtained through the Group Embedded Figures Test (GEFT), while the covariational reasoning data obtained through the covariational problem test and verified by several interviews. The results showed that there was no significant consistent difference between field-dependent and field-independent students in their covariational reasoning level, but there were differences in students’ way of reacting to the context of the problems. Field-dependent subjects exhibited their mental action inconsistently when they faced a new problem that more complex than before. This finding indicated that we need to set the problem to make it an effective stimulus in developing student’s covariational reasoning ability.